Students’ Ability and Difficulties in Reading Narrative Text in SMA Kristen Petra Kefamenanu - Aurelia Erica B. A. Soares; Imanuel Kamlasi; Delti Yulita (CV. Samuel Manurung and Co, 2023)
The purpose of this study was to examine students’ ability and difficulties in reading narrative text in SMA Kristen Petra Kefamenanu. It develops a way of reading English narrative texts through short stories as a medium of learning for students. This research used classroom action research. This classroom action research was carried out in 2 cycles. Each cycle consists of four steps, namely planning, action, observation, and reflection. This research technique uses a short story test consisting of multiple choices. The test consisted of cycle I and cycle II. This study analyzed the average score of each test to determine the increase in students' vocabulary in the short story narrative text after the action is taken. The results showed that narrative texts could improve students' vocabulary, which was seen in the results of the student's average score in Cycle I was 92 and in Cycle II was 92. It is concluded that teachers chose short story narrative texts to learn and teach vocabulary as one of the techniques to improve students' reading skills.